Signa Vitae 2020
DOI: 10.22514/sv.2020.16.0002
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarticular Infections in Newborns: Prognostic Factors and Outcome

Abstract: Purpose: To analyze clinical, laboratory, microbiologic, imaging and therapeutic data that contribute to outcome in newborn infants with osteoarticular (OSA) infection. Methods: Clinical course, imaging and follow-up data of 15 newborns with the diagnosis of OSA infection were retrospectively reviewed. Results: 15 newborns with 23 acute osteoarthritis foci were included: risk factors were identified in 73%, lower extremities were affected in 8 (53%) and more than half of the children had two-or multifocal invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In recent years, prevalence of AGA has increased. 3,4 A study conducted by Gonzalez has reported that MSU crystal deposition in the synovium or joints could increase the expression of inflammatory cytokines, including interleukin 1β (IL-1β), interleukin 6 (IL-6), and tumor necrosis factor α (TNF-α), eventually resulting in the occurrence and development of AGA. 5 Therefore, inhibiting of MSU crystal deposition-induced inflammatory response is one potential therapeutic method for the treatment of AGA.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, prevalence of AGA has increased. 3,4 A study conducted by Gonzalez has reported that MSU crystal deposition in the synovium or joints could increase the expression of inflammatory cytokines, including interleukin 1β (IL-1β), interleukin 6 (IL-6), and tumor necrosis factor α (TNF-α), eventually resulting in the occurrence and development of AGA. 5 Therefore, inhibiting of MSU crystal deposition-induced inflammatory response is one potential therapeutic method for the treatment of AGA.…”
Section: Introductionmentioning
confidence: 99%